Pedagogical and psychological aspects of students' creative abilities (Pedagogy of Higher and Secondary Education, 2009)
The article touches upon the importance of developing students‘ creativity аs an essential part of forming an educated, creative personality, his/her intellectual potential, proses the importance of pedagogical and psychological aspects of developing the students' creativity as a driving force for improving the creative potential of students.
Keywords: creative work; creative personality; development of creativity